2015
DOI: 10.15171/ijhpm.2015.151
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy Impact on National Healthcare Utilization and Expenditure

Abstract: Background: Health literacy presents an enormous challenge in the delivery of effective healthcare and quality outcomes. We evaluated the impact of low health literacy (LHL) on healthcare utilization and healthcare expenditure. Methods: Database analysis used Medical Expenditure Panel Survey (MEPS) from 2005-2008 which provides nationally representative estimates of healthcare utilization and expenditure. Health literacy scores (HLSs) were calculated based on a validated, predictive model and were scored accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
137
2
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(161 citation statements)
references
References 31 publications
5
137
2
4
Order By: Relevance
“…HL has been found to be inversely associated with healthcare utilization and expenditure [10e12, 25,29,30]. We found that this was also true for COPD, since those with inadequate HL suffered more comorbidities, had more visits to emergency departments and hospital admissions and were more dependent ( Table 2).…”
Section: Discussionmentioning
confidence: 51%
“…HL has been found to be inversely associated with healthcare utilization and expenditure [10e12, 25,29,30]. We found that this was also true for COPD, since those with inadequate HL suffered more comorbidities, had more visits to emergency departments and hospital admissions and were more dependent ( Table 2).…”
Section: Discussionmentioning
confidence: 51%
“…Since low health-related literacy is considered to be pervasive and unmodifiable short of reforming education systems, research has generally ignored empowerment. Rather, patients' low literacy has been posited as an explanation for inequities and disparities, low quality, [2] poor outcomes [6], and high costs [25]. This deficit approach is disempowering to all concerned.…”
Section: Health Empowerment -Interactive and Reflective Skillsmentioning
confidence: 99%
“…Rasu et al [28] agree that high literacy likely goes along with higher use of preventive care and thus, in the long run, with lower utilization; however, upward they point out that the correlation can also be explained by the increasing use of electronic media such as the Internet to help manage symptoms and conditions.…”
Section: Introductionmentioning
confidence: 99%